Clinical and Therapeutic Characteristics of Pituitary TSH-Secreting Adenoma in Adolescent-Onset Patients: Six Case Studies and Literature Review - Yang, Yamei; Liu, Jie; Deng, Kan; Lu, Lin; Zhu, Huijuan; Lian, Xiaolan; Bao, Xinjie; Duan, Lian; Yao, Yong (Frontiers in Endocrinology, 2021)
Background Thyrotropin-secreting adenoma (TSH-oma) is a very rare kind of functional pituitary adenoma, especially that which occurs in adolescents. However, its potential clinical and therapeutic characteristics are still unknown. Objectives The study was aimed to summarize the clinical and therapeutic characteristics of patients with adolescent-onset TSH-oma. Methods We retrospectively analyzed six (4.1%) adolescent-onset TSH-oma cases from 148 patients who were diagnosed with TSH-oma at our hospital between January 2012 and October 2020. A literature review was performed on the PubMed online database, and 14 adolescent-onset TSH-oma cases were retrieved. Then, the characteristics of clinical manifestations, treatment outcomes, and follow-ups were analyzed and compared to the adult TSH-oma patients. Results Altogether, 20 adolescent-onset cases were included in this study having mean onset age of 13.4 ± 3.3 years. Males were found to be slightly predominant (M: F = 1.5:1) in our study. The median baseline levels of TSH, FT3, and FT4 in adolescent-onset cases were found to be 6.30 [interquartile range (IQR) 9.82] µIU/ml, 9.18 (IQR 11.61) pg/ml, and 3.22 (IQR 1.90) ng/dl, respectively, which were all significantly higher than the adult patients of our hospital. Also, the adolescent-onset cases showed more large tumor ratio (36.8% vs. 9.3%, p = 0.007) compared to the adult patients. Compared to the patients of all ages in the literature, the biochemical remission rate of SSAs (57.1%) and remission rate of TSS (38.9%) were found to be considerably lower in adolescent-onset patients, while the recurrence rate (44.4%) was found to be considerably higher. Conclusions Adolescent-onset TSH-oma patients showed higher TSH and thyroid hormone levels, more large tumors, and worse treatment outcomes than adult cases. Hence, early diagnosis, multidisciplinary therapy, and close follow-up should be highlighted to improve the prognosis.